A surrogate BSL2-compliant infection model recapitulating key aspects of human Marburg virus disease - Wanying Yang; Wujie Zhou; Bo Liang; Xiaojun Hu; Shen Wang; Zhenshan Wang; Tiecheng Wang; Xianzhu Xia; Na Feng; Yongkun Zhao; Feihu Yan (Emerging Microbes and Infections)
Marburg virus disease (MVD) is a severe infectious disease caused by the Marburg virus (MARV), posing a significant threat to humans. MARV needs to be operated under strict biosafety Level 4 (BSL-4) laboratory conditions. Therefore, accessible and practical animal models are urgently needed to advance prophylactic and therapeutic strategies for MARV. In this study, we constructed a recombinant vesicular stomatitis virus (VSV) expressing the Marburg virus glycoprotein (VSV-MARV/GP). Syrian hamsters infected with VSV-MARV/GP presented symptoms such as thrombocytopenia, lymphopenia, haemophilia, and multiorgan failure, developing a severe systemic disease akin to that observed in human MARV patients. Notably, the pathogenicity was found to be species-specific, age-related, sex-associated, and challenge route-dependent. Subsequently, the therapeutic efficacy of the MR191 monoclonal antibody was validated in this model. In summary, this alternative model is an effective tool for rapidly screening medical countermeasures against MARV GP in vivo under BSL-2 conditions.